PENGARUH JENIS DAUN DAN PELARUT TERHADAP RENDEMEN EKSTRAK SAPONIN DAUN PEPAYA (CARICA PAPAYA LINN.) - fithriyani, dina (Edible: Jurnal Penelitian Ilmu-ilmu Teknologi Pangan, 2021)
Food safety issues can not be separated from the microbial pathogens that can cause health problems and food spoilage. Their presence in food product should be prevented and controlled. One of the efforts to improve food safety is the utilization of antimicrobial compounds, that can inhibit the growth of pathogenic microbes and food spoilage microorganism like Saponin. Saponins are triterpenic or steroidal glycosides which have many biological properties, and largely distributed in papaya leaves abundantly grown in Indonesia. This research aimed to compare the extraction procedure of saponin from papaya leaves by the difference of papaya leaves (young and old) and solvent (methanol, ethanol) that be used. The results showed that extraction by etanol provided higher yields (5.7 %) than by metanol (3.2 %). The yields of saponin-rich-extract from young and old leaves were not significantly different. Keywords: saponin, extract, ethanol, methanol, papaya leaves